Dielectric relaxation and polaronic conduction in epitaxial BaFe12O19 hexaferrite thin film. (17th February 2016) - Tang, Rujun; Zhou, Hao; Zhao, Run; Jian, Jie; Wang, Han; Huang, Jijie; Fan, Meng; Zhang, Wei; Wang, Haiyan; Yang, Hao
Abstract: The dielectric properties of epitaxial BaFe12 O19 hexaferrite thin film have been investigated as a function of frequency (50 Hz − 2 MHz) and temperature (100–375 K). The frequency dependent permittivity, impedance ( ) and modulus ( ) spectra show that the dielectric responses of BaFe12 O19 thin film are thermally activated. The activation energy of BaFe12 O19 film ( E a ) is much smaller than that of the polycrystalline bulk BaFe12 O19 . In addition, E a increases with increasing temperature and there is a distribution of relaxation time in the sample. The scaling behavior of and spectra of the sample further suggest that the distribution of relaxation time is temperature independent at low temperatures (<250 K) and temperature dependent at high temperatures. The temperature dependent dc conductivity shows that small polaron hopping is the most probable conduction mechanism for BaFe12 O19 film.